(untitled) (Research, Society and Development, 2024)
Dermatophytes, the causative agents of dermatophytosis, are keratinophilic fungi that use keratin as a substrate for their development and therefore can easily colonize soil enriched with skin, hair, nails, feathers, hooves, and other keratinized materials. Considering that they are important zoonotic pathogens and that the soil is an important factor in the dissemination and propagation of this disease, the present work aimed to isolate dermatophyte fungi in samples collected from the homes of riverside communities in the states of Acre and Amazonas. 23 soil samples were collected from places where the population carries out their main daily activities and subsequently sent to the UFRRJ Clinical Mycology Laboratory. In the methodology, the technique described by Vanbreuseghem was used, where a sufficient amount of soil was placed in sterile glass Petri dishes until the bottom was completely covered. Horse sterile hair was then added and mixed with the moistened soil. Within 15 days after the initial processing, the emergence of colonies could be observed. Identification was carried out through macromorphological analysis of colonies and microscopy. Of the 23 samples analyzed, dermatophytes were identified in 5. Among the isolates are Nannizzia gypsea, Nannizzia nana and Trichophyton spp. that were tested to evaluate antifungal resistance. Having confirmed soil contamination, this study highlights the need for greater investment in research, in addition to continuous monitoring of the soil, with the aim of identifying the presence of these potential pathogens in the region and establishing measures to control and prevent dermatophytosis.